MARKET ANALYSIS ON SUPPLY CHAIN OF PISANG MAS FROM LUMAJANG REGENCY, EAST JAVA - Kuntoro Boga Andri (UNEJ e-Proceeding, 2012)
The purpose of this study was to determine the supply chain model and the pattern of “Pisang Mas” or Golden Bananas marketing in Lumajang, as well as to recognize the role and functions of the existing supply chain players in the system. The research was carried by conducting survey to agribusiness and contract players such as farmers, traders, collectors, distributors, partner companies and traders from outside these regions whooperated their business in these regions. The result showed that agribusiness of this bananas in the studied areas would be giving a greater economic benefit. The pattern of contract marketing gave a better benefit to farmers and marketing partner companies than other pattern. This model required business improvement and corporate partners should participate in the improvement from cultivation to marketing activities.